Investigating the mediating role of spouse\'s perceived responsiveness in the relationship between the health of the family of origin and marital quality - Akram Narimani; Esmaeil Asadpour; Zohreh Sadeghi Afjeh; Kambiz Poushaneh (مجله علوم روانشناختی, 2023)
Background: According to previous studies, the health of the family of origin and the spouse's perceived responsiveness are among the relevant and influencing variables on marital quality. The role of the aforementioned variables on the marital quality of couples has been studied, but there is a research gap regarding the mediating role of the spouse's perceived responsiveness in the relationship between the health of the family of origin and marital quality. Aims: The present study was conducted with the purpose of investigating the mediating role of spouse's perceived responsiveness in the relationship between the health of the family of origin and marital quality. Method: The research method was descriptive-correlation and structural equation modeling. The statistical population included all married women who referred to counseling centers in 2022 in Tehran city, and 397 of them were selected by convenience sampling method. To collect data, Family–Of-Origin (Hovestadt et al., 1985), Marital Quality Scale (Busby et al., 1995) and Perceived Partner Responsiveness Scales (Reis et al., 2017) were used. Structural equation modeling and SPSS22 and Amos22 software were used for data analysis. Results: Structural equation modeling showed that the health of the Family of origin has a significant effect on women's marital quality both directly and indirectly (through perceived responsiveness) (p<0/01). Conclusion: According to the obtained results, it seems that the health of the family of origin has a direct and indirect effect on the marital quality through the mediation of improving the spouse's perceived responsiveness. The health of the family of origin as a supporting factor, in turn leads to the spouse's perceived responsiveness, and the person shows a higher marital quality due to the positive emotions caused by them.